Technology (Chicago Encyclopaedia Britannica, 2011)
Updated for 2011, Technology, is one book in the Britannica Illustrated Science Library Series that covers today's most popular science topics, from digital TV to microchips to touchscreens and beyond. Perennial subjects in earth science, life science, and physical science are all explored in detail. Amazing graphics-more than 1,000 per title-combined with concise summaries help students understand complex subjects. Read more
Science
1 2 5 8 12 13 15 17 18 20 21 22
NEW_ZTN_GN
Keywords: Information technology; Science; Technology -- Science